Second Hand Smoke Exposure at UWEC - Steffen, Kelly; Aragon, Sara; Bloecher, Pat; Sisbach, Matt (My University, 2010)
Secondhand cigarette smoke is associated with a spectrum of lung diseases including lung cancer, as well as cardiovascular disease. While designated smoking areas on campus have been established to protect smokers? rights, secondhand exposure to others is common along walkways and in buildings where smoke enters through air intake vents.
Secondhand Smoke Exposure at the University of Wisconsin-Eau Claire
Color poster with text, images, and tables.
Keywords: Passive smoking--Wisconsin--Eau Claire; Passive smoking--Health aspects--Wisconsin--Eau Claire; University of Wisconsin--Eau Claire--Students--Health risk assessment; University of Wisconsin--Eau Claire--Employees--Health risk assessment; Posters